Immune Response of Nipah Worms (Namalycastis rhodochorde) Following Injection of Pseudonocardia spp.: Indonesia - Wiranata, Aufar Ismi; Dea, Uray; Nabila, Vioni Talitha; Putri, Fiqih Fazira; Wibowo, Raynata Zwietenia; Yanti, Ari Hepi (Jurnal ILMU DASAR, 2025)
The nipah worm (Namalycastis rhodochorde) is a Polychaete species found in the nipah (Nypa sp.) mangrove ecosystem of West Kalimantan. Since its identification in 2007, research on this species has been limited. Nipah worms play a crucial role in trophic levels, serving as a food source for various aquatic animals due to their high nutritional content. Although attempts have been made to cultivate nipah worms, these efforts are still hindered by disease outbreaks, one of which is caused by a bacteria. This study aims to investigate the immune response of nipah worms following induction with Pseudonocardia spp. isolated from nipah fronds. The research methodology included the preparation of tools and materials, acclimation of nipah worms, reculturing of Pseudonocardia spp. and the creation of test suspensions, as well as the calculation of the total and differential counts of coelomocytes before and after bacterial induction. The results indicated an increase in the number of several types of coelomocytes in nipah worms, specifically type I by 53,2%, type III by 54%, type IV by 56,2%, and type V by 61,4% after induction with Pseudonocardia spp.